Cellular and humoral immune response between snail hosts and their parasites - Al-Khalaifah, Hanan (Frontiers in Immunology, 2022)
In invertebrates, the innate immune system protects against a wide range of microbiological infections. Several immunological processes are involved in the interactive immune response between snails and their parasites, including phagocytosis, nitric oxide synthesis, phenol oxidase activity, lysozymes, and lectin formation. However, these immune responses are usually ineffective in parasite elimination. The immunological responses connected to the interaction between snails and parasites are discussed in detail in the current research. Understanding the nature of these interactive reactions will enable scientists to explore approaches to eliminate and cure parasitic infections.